ANALISIS KUALITATIF KADAR OBAT DENGAN METODE TITRASI ACIDI-ALKALIMETRI - Rahmadani Rahmadani; Fitria Kasim; Reza Febrianti; Nurfadhila Arsyad; Ahmad Virgiawan; Jum Aprilianti; Putri Nadya Shifa; Marhamah Muh Yasrin; Nur Ainun Mutmainah; Rainy Alkiswah Hafid; Firda Firda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Medicines are substances that can be used to treat or cure a disease, reduce symptoms, or alter chemical processes in the body. There are various methods of determining the concentration or level of a drug preparation. Acidi-alkalimetric is a standart titration method to determine the level of acidic or basic analytes based on acid and bade reaction. The study aims to determine the levels of several types of drugs using the principle of acidi-alkalimetric.. The results of the concentration levels of Aspilet 80 mg, Bodrex and Vicee 500 mg with the Acidi-Alkalimetric Titration Method where the resulting concentration levels of Aspilet 80 mg are 93,74 mg, Bodrex is 93,308 mg and Vicee 500 mg is 1.490 mg which means none of the three drugs meet the requirements in the Indonesian pharmacopoeia.